A centroid-based gene selection method for microarray data classification. (7th July 2016) - Guo, Shun; Guo, Donghui; Chen, Lifei; Jiang, Qingshan
Abstract: For classification problems based on microarray data, the data typically contains a large number of irrelevant and redundant features. In this paper, a new gene selection method is proposed to choose the best subset of features for microarray data with the irrelevant and redundant features removed. We formulate the selection problem as a L1-regularized optimization problem, based on a newly defined linear discriminant analysis criterion. Instead of calculating the mean of the samples, a kernel-based approach is used to estimate the class centroid to define both the between-class separability and the within-class compactness for the criterion. Theoretical analysis indicates that the global optimal solution of the L1-regularized criterion can be reached with a general condition, on which an efficient algorithm is derived to the feature selection problem in a linear time complexity with respect to the number of features and the number of samples. The experimental results on ten publicly available microarray datasets demonstrate that the proposed method performs effectively and competitively compared with state-of-the-art methods. Highlights: A gene selection method is proposed by using centroid-based discriminant criterion. Kernel-based expectation is used to estimate the class centroid. An efficient algorithm is proposed for the L1-regularized optimization problem. Theoretical analysis indicates that the global optimal solution can be reached. Our method has linear complexity with the number of genes and samples.